(untitled) (Bangladesh Journal of Microbiology, 2019)
Antibiotic resistant E. coli are prevalent in Bangladesh. The indiscriminate use of antimicrobials and ready availability of over the counter drugs are responsible for this. This study was conducted to investigate the susceptibility of clinical Escherichia coli to the antibiotics Imipenem, Ceftriaxone, Ceftazidime and Azithromycin. Kirby-Bauer disk diffusion method was used to determine sensitivity to antimicrobials. Agar based assay was employed for the detection of efflux pumps. PCR was used amplify antibiotic resistance genes.All isolates were resistant to Ceftriaxone whereas most were sensitive to Imipenem. The MICs of Ceftazidime and Azithromycin ranged between 128 μg/ml and 256 μg/ml. The prevalence of ²-lactamase producers was 57.89 % with 36.84 % of the isolates exhibiting ESBL activity. No specific correlation could be found between plasmid sizes and antibiotic resistance patterns. Efflux pump was found to be involved in Azithromycin resistance in 63.15% of the isolates. The gene for phosphotransferase, mph(A) was the most common among the macrolide modifying genes, being present in 73.68% (14/19) of the isolates followed by both erm(A) anderm(C) esterases each present in 10.53% (2/19) isolates. This study concluded that clinical isolates of E. coli in Bangladesh could be resistant to multiple classes of antibiotics through different mechanisms of resistance. Bangladesh J Microbiol, Volume 34 Number 2 December 2017, pp 61-66